2011
DOI: 10.1016/j.ejvs.2010.12.009
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cerebral Oximetry in Combination with Awake Testing in Patients Undergoing Carotid Endarterectomy under Local Anaesthesia

Abstract: Cerebral oximetry using a cut off ≥19% drop in rSO(2) has a high sensitivity and specificity when compared with awake testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 38 publications
6
32
2
Order By: Relevance
“…Several report rScO 2 during carotid surgery (Williams et al, 1994a,b,c, 1999; Duncan et al, 1995; Kuroda et al, 1996a; Mead et al, 1996; Samra et al, 1996; Duffy et al, 1997; Beese et al, 1998; Carlin et al, 1998; de Letter et al, 1998; Fearn et al, 2000; Takeda et al, 2000; Kawada et al, 2002; Cuadra et al, 2003; Ogasawara et al, 2003; Vets et al, 2004; Komoribayashi et al, 2006; Yamamoto et al, 2007; Ishigaki et al, 2008; Lee et al, 2008; Stoneham et al, 2008; Kobayashi et al, 2009; Giustiniano et al, 2010; Moritz et al, 2010; Ali et al, 2011; Ritter et al, 2011; Pedrini et al, 2012; Uchino et al, 2012). …”
Section: Resultsmentioning
confidence: 99%
“…Several report rScO 2 during carotid surgery (Williams et al, 1994a,b,c, 1999; Duncan et al, 1995; Kuroda et al, 1996a; Mead et al, 1996; Samra et al, 1996; Duffy et al, 1997; Beese et al, 1998; Carlin et al, 1998; de Letter et al, 1998; Fearn et al, 2000; Takeda et al, 2000; Kawada et al, 2002; Cuadra et al, 2003; Ogasawara et al, 2003; Vets et al, 2004; Komoribayashi et al, 2006; Yamamoto et al, 2007; Ishigaki et al, 2008; Lee et al, 2008; Stoneham et al, 2008; Kobayashi et al, 2009; Giustiniano et al, 2010; Moritz et al, 2010; Ali et al, 2011; Ritter et al, 2011; Pedrini et al, 2012; Uchino et al, 2012). …”
Section: Resultsmentioning
confidence: 99%
“…A cut off ≥19% drop in regional oxygen saturation has a high sensitivity and specificity when compared with awake testing (17). Another study identified a cut-off of 21 and 10.1% reduction from the baseline as optimal when deciding whether patients needed or not a shunt regarding the first and fifth minute after cross-clamping, respectively (18).…”
Section: Discussionmentioning
confidence: 99%
“…It has also shown its correlation with EEG changes, transcranial Doppler, carotid stump pressure and postoperative neurological deficits [29,[30][31][32][33]. The sensitivity of this test ranges from 30 to 100% according to various studies and its specificity between 77 and 98% [29,[30][31][32][33][34][35][36]. The limit value is not well established, although several studies suggest a decrease of 11.7-25% above baseline value [29,30,[34][35][36].…”
Section: Near Infrared Spectroscopy (Nirs)mentioning
confidence: 99%
“…The sensitivity of this test ranges from 30 to 100% according to various studies and its specificity between 77 and 98% [29,[30][31][32][33][34][35][36]. The limit value is not well established, although several studies suggest a decrease of 11.7-25% above baseline value [29,30,[34][35][36]. This method has the advantage of being non-invasive, continuous and easy to interpret but the fact of collecting information of the frontal lobe, behaves as a disadvantage as it leaves the parietal lobe unmonitored, being the most sensitive lobe to ischemia during carotid surgery [34].…”
Section: Near Infrared Spectroscopy (Nirs)mentioning
confidence: 99%